AN INTERPRETATION OF THE VALUE ABOUT PHYSICAL EDUCATION CLASSES FOR TEENAGERS WHO ARE INVOLVED IN PROBLEMS OF BEHAVIORAL UPSET IN A SCHOOL (Fiep Bulletin - online, 2015)
Violence is part of Human Being's character. So, there must be a change in how the educator behaves and acts in order to control violence. The aim of this process of education may be achieved by the comprehension of Humans' moral needs. This paper presents some specific cases of violence among teenager's of 12 to 15 years old who show some troubles to match the pedagogic proposals of the municipal school Jardim Gláucia, in Belfort Roxo, concerning the integration and interaction with each other. It can be assumed that these teenagers were segregated many times for the reason of having existential problems caused by some behavioral problems and that there is a direct relation between such problem and the their social-historic needs and, as long as one is able to understand violence and such disturbances by this point of view, Physical Education classes become a valid pedagogical instrument for students' education.
Keywords: Violence; Human Lacks and Physique Education.